THE SPIRITUAL FACTOR IN EDUCATIONAL ADMINISTRATION - Thom, Douglas J. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1984)
"The best lack all conviction, while the worst are full of passionate intensity." Yeats was possessed of a gloomy but not uncommon foreboding about our times when he wrote those lines, anticipating a joyless Second Coming by some rough, unknown, slouching beast. Can one have convictions of a spiritual sort without the passionate intensity that is associated - in the minds of many - with the word "religious"? The difficulty, in Thom’s view, has delayed too long the recognition that people in positions of leadership in education cannot manage their full responsibilities on technique alone. They must have conviction about the rightness of what they do, a conviction communicated to those working with and under them; and education must be animated once more by the idea of service. He cites a number of current thinkers and practitioners who maintain, as he does, that being spiritual is a necessary condition for the really effective administrator. RÉSUMÉ "Les meilleurs manquent totalement de convictions tandis que les pires sont intensément passionnés." Les prémonitions de Yeats étaient plutôt: lugubres mais certainement pas rares lorsqu’il écrivit ces lignes, prévoyant le second Avmement sans joie d’une bête brutale, inconnue et rustre. Peut-on avoir des convictions de nature spirituelle sans l’intensité passionnée qui va de pair, de l’avis de beaucoup, avec le terme "religieux"? La difficulté, selon Thom, a différé pendant trop longtemps l’admission que les gens occupant des postes de direction dans l’éducation ne peuvent s’acquitter de leurs pleines responsabilités avec la technique seulement. Ils doivent être convaincus de la justesse de ce qu’ils font, et transmettre cette conviction à ceux qui travaillent avec eux et sous leurs ordres; et l’éducation doit être animée une fois de plus par l’idée de service. Il cite un certain nombre de penseurs et de praticiens actuels qui soutiennent, comme lui, que la spiritualité est une condition nécessaire à tout administrateur qui se respecte.